2022
DOI: 10.3390/ma16010063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recycled Rubber Particles Incorporated as Partial Sand Replacement on Fresh and Hardened Properties of Cement-Based Concrete: Mechanical, Microstructural and Life Cycle Analyses

Abstract: Cement is one of the most valuable materials in today’s society, as it is used in most construction developments known to mankind. However, the energy intensive process and significant environmental impacts related to the production of Ordinary Portland Cement have shown the importance of searching for more sustainable materials. Concrete uses different aggregates added to the cement binder to lower, not only cost, but other factors like environmental burden, while maintaining good mechanical properties. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Results of the compression test conducted on the specimens are shown in Figure 10. The results are similardecreasing with increase in the percentage of WCR replacement -to that of crushed clay brick for sand replacement done by GARCIA-TRONCOSO et al [45], OLOFINNADE et al [46] and ZHU and ZHU [47].…”
Section: Compressive Strengthsupporting
confidence: 64%
“…Results of the compression test conducted on the specimens are shown in Figure 10. The results are similardecreasing with increase in the percentage of WCR replacement -to that of crushed clay brick for sand replacement done by GARCIA-TRONCOSO et al [45], OLOFINNADE et al [46] and ZHU and ZHU [47].…”
Section: Compressive Strengthsupporting
confidence: 64%
“…In [1], it is indicated that while rubber is a material that causes pollution, crushed rubber in recycled products helps reduce its negative impact on the environment. In a study conducted by [2], the viability of replacing fine aggregate with recycled rubber in different proportions in concrete is demonstrated without significantly affecting its compressive and flexural strength. [3] considered the possibility of replacing rubber for half of the total fine aggregate to promote the circular economy.…”
Section: Literature Reviewmentioning
confidence: 99%